(untitled) (Advances in Applied Biological Research, 2025)
The risk of deep vein thrombosis (DVT) in women is strongly associated with pregnancy, the risk increasing by 5 to 10 times. This risk then gradually increases until it peaks during and after delivery. Blood clots are one of the most feared complications after childbirth. They usually occur in the legs or pelvis and can dislodge and travel to the lungs, causing pulmonary embolism. It can be controlled on this state by using blood-thinning medications to avoid death. This problem occurs as one complication of a cesarean section, which involves a surgical technique for delivering a baby through an incision in the abdomen and uterus. It is performed as an alternative to vaginal delivery. Although the risk of venous thromboembolism increases with surgical delivery, there is no consensus on the prevention of clots after cesarean section.